2021
DOI: 10.5603/gp.a2021.0135
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 pandemic on reproductive intentions among the Polish population

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Ginekologia Polska" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 10 publications
(11 reference statements)
1
21
0
Order By: Relevance
“…It has led to an increased interest in infectious diseases and prevention, but also to a change in reproductive intentions. Many couples have postponed their plans to have children, reduced the number of children they initially planned to have, or decided not to have children at all [7]. On 27 December 2020, the vaccination program against COVID-19 began in Poland, and now COVID-19 vaccination is also recommended for pregnant women [8].…”
Section: Introductionmentioning
confidence: 99%
“…It has led to an increased interest in infectious diseases and prevention, but also to a change in reproductive intentions. Many couples have postponed their plans to have children, reduced the number of children they initially planned to have, or decided not to have children at all [7]. On 27 December 2020, the vaccination program against COVID-19 began in Poland, and now COVID-19 vaccination is also recommended for pregnant women [8].…”
Section: Introductionmentioning
confidence: 99%
“…These differences aside, the reversing in this age trend associated with the first COVID-19 case surge bolsters early evidence suggesting that, early in the pandemic, people’s openness toward the prospect of pregnancy was reduced. 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 Notably, in the US Southwest, COVID-19 case rates remained low around April 2020, when the shelter-in-place mandate went into effect, and the curtailing of the DAP score decline occurred 3 months later during the first surge in COVID-19 cases in the region. This timing suggests individuals’ pregnancy preferences may have been associated more with increasing regional COVID-19 case rates than shelter-in-place mandates enacted in response to high case rates nationally.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of cross-sectional, usually internet-based, survey research has found that reports of modified pregnancy desires were common early in the pandemic. Conducted in the US 6 , 7 , 8 and other countries in the Northern Hemisphere, 9 , 10 , 11 , 12 , 13 these surveys have broadly found up to one-half of respondents reporting that their desire for pregnancy declined (or that they wanted to postpone pregnancy), citing health risks, financial concerns, loss of income, and sense of uncertainty about the future. At the same time, these studies have found smaller proportions of respondents reporting increased desire for pregnancy because of the pandemic, owing to wanting change and positivity in their life, lower opportunity costs of taking time off work for child-rearing, and a recalibration of priorities.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting survey was conducted by Sienicka et al [ 30 ], wherein 22% of a group of 984 participants (males, females, and non-binary individuals) changed their reproductive intentions. In this group, 86.6% were afraid of limited access to prenatal care and delivery services and 81% were afraid of giving birth at the hospital [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…An interesting survey was conducted by Sienicka et al [ 30 ], wherein 22% of a group of 984 participants (males, females, and non-binary individuals) changed their reproductive intentions. In this group, 86.6% were afraid of limited access to prenatal care and delivery services and 81% were afraid of giving birth at the hospital [ 30 ]. This survey, although based on an online questionnaire, shows that limitations in perinatal care have a real impact on the decisions in regard to family planning in Polish society.…”
Section: Discussionmentioning
confidence: 99%